Chef : powerful infrastructure automation : deploy software, manage hosts, and scale your infrastructure with Chef : a course in three modules.: powerful infrastructure automation : deploy software, manage hosts, and scale your infrastructure with Chef : a course in three modules. (2017) - Ewart, John; Marschall, Matthias; Waud, Earl
No abstract available